Promotions in action: classifying promotional activities from consumers' perspective - Anauate, Patricia Montagna (2020)
Objective: To investigate the perception and classification criteria of different sales promotions types undertaking consumers' point of view. Method: After analyzing literature and gathering market data, primary data was obtained with an online questionnaire and systematically analyzed with the interpretation and search for patterns in the data. This process enabled the identification of core themes or classification forms of sales promotions adopted by consumers. Originality/Relevance: This article brings a new perspective to the classification of different promotion types, presenting an analysis from consumers’ perpective whereas prior studies presented punctual and binary classifications, generally focusing on the results derived from promotions for the company. Results: A matrix with four groups of sales promotions was generated based on the two classification criteria most cited by consumers - type of benefit in terms of execution time (immediate or future) and whether there is a direct relationship with the product itself or not. Theoretical/ methodological contributions: This research consolidates into a single analysis several prior studies on the types, classification and effects of sales promotions, combining these different reflections in the literature and offering an understanding on the subject under the empirical perspective of consumers. Social contributions / contribution to management: This study contributes to the guidance of brand managers when developing marketing plans, more specifically the promotion strategy